Mapping the Role of Intellectuals in Iranian Modern and Contemporary History - Jahanbegloo, Ramin (Lexington Books, 2020)
This book analyzes the role of intellectuals as the prime mediators between the forces of tradition and modernity in twentieth century and twenty-first century Iran.